Evaluation of tea cups washing water contamination to fecal coliform at traditional tea shops in Sari, Iran - Z. Yousefi; A.A. Ghanbari (Journal of Mazandaran University of Medical Sciences, 2006)
Background and purpose: Most traditional tea shop owners use a bowl to wash tea cups in Sari city (North of Iran). There are more than 140 traditional tea shops in the city. Unfortunately most people drinking at these shops as well as health authorities do not pay attention to the health criteria of the shop. The objective of this study was to examin the tea cups washing water of traditional tea shops for contamination to fecal coliform in Sari city.Materials and Methods: Twenty traditional tea shops (16%) were randomly selected for this study in different areas of the city. Multistage (3 stages) samples were taken from tea set of the shops. All samples were collected from the tea sets of the shops without prior notice. The samples were transferred to the laboratory in cold box as quickly as possible.Results: Forty four samples from a total of 60 (66.6%) were positive for total coliforms. Also 32 samples (33.3%) were positive for fecal coliforms. Number of bacteria in the samples varied from zero to over 1100 per 100 cc sample. The study showed that in warmer situations the contamination was higher. The results showed that the differences between contamination rates in both groups of internal and external traditional tea shops were insignificant.Conclusion: The results showed that only two samples in multistage sampling were not contaminated and in all other samples at least in one stage of sampling, contamination was detected. The results of this study is an important message for food administration.